Obitury - Lamichhane, Nirmal (Nepalese Journal of Cancer, 2026)
It is with profound sorrow that we announce the passing of Dr. Prakash Raj Neupane, an eminent surgical oncologist and a towering figure in the field of cancer care in Nepal. His demise marks an irreparable loss not only to the medical fraternity but also to the countless patients and families whose lives he touched with compassion, skill, and dedication.